The Effect of Enterprise Risk Management and Environmental Performance Toward Corporate Social Responsibility Disclosure (CSRD): Study in Mining Sector - Sirli Anillah; Ratna Septiyanti; Yenni Agustina (PT FORMOSA CENDEKIA GLOBAL, 2023)
The population is 47 Mining companies in IDX 2016-2018. Have PROPER rating and published annual report. The purpose to examine the effect of enterprise risk management(ERM) and environmental performance (EP) toward CSR Disclosure. Data were obtained from 63 samples and used sample selection method, purposive sampling method and IBM SPSS 26. The analysis statistic used is multiple linear regression analysis method. The ERM used COSO ERM Framework to disclosure 108 items, EP used PROPER rating represent in 5 ranking and CSRD used GRI G4 CSR index consisting 91 items, 3 categories. The study result shows that ERM have positive and significant effect on CSRD, while EP does not have significant affect on CSRD.